2022
DOI: 10.1186/s42234-022-00095-x
|View full text |Cite
|
Sign up to set email alerts
|

Delivering transcutaneous auricular neurostimulation (tAN) to improve symptoms associated with opioid withdrawal: results from a prospective clinical trial

Abstract: Background As pharmacological treatments are the primary option for opioid use disorder, neuromodulation has recently demonstrated efficacy in managing opioid withdrawal syndrome (OWS). This study investigated the safety and effectiveness of transcutaneous auricular neurostimulation (tAN) for managing OWS. Methods This prospective inpatient trial included a 30-minute randomized, sham-controlled, double-blind period followed by a 5-day open-label pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…There was a more significant reduction in the COWS of the active tAN group than that in the sham group after 30 min of stimulation (reduced by 6.3 compared to 3.7, p = 0.036). 94 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a more significant reduction in the COWS of the active tAN group than that in the sham group after 30 min of stimulation (reduced by 6.3 compared to 3.7, p = 0.036). 94 …”
Section: Resultsmentioning
confidence: 99%
“…There was a more significant reduction in the COWS of the active tAN group than that in the sham group after 30 min of stimulation (reduced by 6.3 compared to 3.7, p = 0.036). 94 Two other trials evaluated alternative anatomical locations. Gazi et al investigated transcutaneous cervical vagus nerve stimulation (tcVNS) in individuals with OUD whose last opioid use was at least 8 hours prior.…”
mentioning
confidence: 99%
“…VNS, vagus nerve stimulation; FDA, Food and Drug Administration; COVID-19, coronavirus disease 2019; ns, non-significant effect on study measure outcome. Reference number , 1 (Addorisio et al, 2019 ), 2 (Arsava et al, 2022 ), 3 (Badran et al, 2020 ), 4 (Chang et al, 2021 ), 5 (Courties et al, 2022 ), 6 (Dawson et al, 2021 ), 7 (De Ridder et al, 2015 ), 8 (Diener et al, 2019 ), 9 (Fisher et al, 2016 ), 10 (Garcia et al, 2021 ), 11 (Gaul et al, 2016 ), 12 (Gazi et al, 2022 ), 13 (Genovese et al, 2020 ), 14 (George et al, 2005 ), 15 (George et al, 2008 ), 16 (Goadsby et al, 2018 ), 17 (Gomolka et al, 2018 ), 18 (Grazzi et al, 2017 ), 19 (Kawai et al, 2017 ), 20 (Kozorosky et al, 2022 ), 21 (Kreuzer et al, 2014 ), 22 (Labar et al, 1999 ), 23 (Lange et al, 2011 ), 24 (Manning et al, 2019 ), 25 (Merchant et al, 2022 ), 26 (Mertens et al, 2022 ), 27 (Morris et al, 2013 ), 28 (Morris and Mueller, 1999 ), 29 (Muthulingam et al, 2021 ), 30 (Najib et al, 2022 ), 31 (Paccione et al, 2022 ), 32 (Redgrave et al, 2018 ), 33 (Rush et al, 2005a ), 34 (Rush et al, 2005b ), 35 (Salama et al, 2020 ), 36 (Shi et al, 2021 ), 37 (Silberstein et al, 2016a ), 38 (Silberstein et al, 2016b ), 39 (Stavrakis et al, 2020 ), 40 (Tassorelli et al, 2018 ), 41 (Tirado et al, 2022 ), 42 (Tornero et al, 2022 ), 43 (Tyler et al, 2017 ), 44 (Verrier et al, 2016 ), and 45 (Wittbrodt et al, 2021 ).…”
Section: Clinical Implications Of Vnsmentioning
confidence: 99%
“…RAVANS was associated with a significant acute reduction in symptoms of depression and anxiety in women with recurrent major depressive disorder (Garcia et al, 2021 ). Regarding opioid withdrawal syndrome, studies have also demonstrated that tcVNS may decrease subjective opioid withdrawal, reduce distress, and lower the heart rate during acute opioid withdrawal (Gazi et al, 2022 ; Tirado et al, 2022 ). Based on the rationale that VNS can activate the LC and catecholamines in the hippocampus and cortex, VNS undergoes some clinical trials to improve cognitive functions in patients with Alzheimer's disease, but these trials did not achieve a conclusive significance (Vargas-Caballero et al, 2022 ).…”
Section: Clinical Implications Of Vnsmentioning
confidence: 99%